Early Middle Ages Houses of Gien (France) from the Inside: Geoarchaeology and Archaeobotany of 9th–11th c. Floors. (2nd April 2020) - Borderie, Quentin; Ball, Terry; Banerjea, Rowena; Bizri, Mélinda; Lejault, Coline; Save, Sabrina; Vaughan-Williams, Alys
ABSTRACT: At Gien (France), indoor floors from early Middle Ages occupation (8th–10th c. AD) are very well preserved, providing a new reference for archaeological investigation in northern France. This site is located on an outcrop, 20 m above the Loire valley, where a 15th c. castle stands now. The medieval occupation combines high-status houses with crafting and agricultural areas. They constitute a new urban nucleus, which grew 2 km east from an ancient Roman settlement. During the rescue excavation, four buildings of different status were sampled and studied using an integrated approach, combining stratigraphy, micromorphology, chemical, macro-remain and phytolith analyses. Micromorphological investigations helped to identify 74 built floors, from 0.5 to 150 mm thick, made with transformed local clay or imported silty earth. Mineral floors were covered by vegetal ones, consisting of crop processing refuse. These litters include an abundance of phytoliths and some seeds, both produced by cultivated cereals, which were processed in situ, such as Triticum durum, Secale cereale and Hordeum vulgare. The refuse above the mineral and vegetal floors were trampled. They were produced not only by domestic activities, such as cooking and eating, but also by metallurgic activities and animal husbandry. The investigation of a contemporary pit indicated that, despite the large amount of refuse, floors were well maintained and regularly rebuilt. The spatial distribution of waste indicated that a single space could be dedicated to several activities, which were not necessarily separated by new floors. Moreover, the total absence of bioturbation allowed the study of a stage of dark earth formation, by comparing it to the contemporaneous mechanical disturbance of a part of the strata which occurred when building new floors. All these results give new evidence of the richness and the complexity of the early Middle Ages town, in addition to help identifying the activities which could take place in early castral areas.